Effect of pig manure on the chemical composition and microbial diversity during co-composting with spent mushroom substrate and rice husks. (March 2018) - Meng, Xingyao; Liu, Bin; Xi, Chen; Luo, Xiaosha; Yuan, Xufeng; Wang, Xiaofen; Zhu, Wanbin; Wang, Hongliang; Cui, Zongjun
Highlights: Pig manure expedited and extended the high temperature period during composting. The addition of pig manure increased the nutrition content of N, P, K and GI. Pig manure provided the essential bacteria as inoculum. Pig manure enriched anti-pathogens at the end of composting. Abstract: In this study, the impact of pig manure on the maturity of compost consisting of spent mushroom substrate and rice husks was accessed. The results showed that the addition of pig manure (SMS-PM) reached 50 °C 5 days earlier and lasted 15 days longer than without pig manure (SMS). Furthermore, the addition of pig manure improved nutrition and germination index. High-throughput 16S rRNA pyrosequencing was used to evaluate the bacterial and fungal composition during the composting process of SMS-PM compared to SMS alone. The SMS treatment showed a relatively higher abundance of carbon-degrading microbes (Bacillaceae and Thermomyces ) and plant pathogenic fungi (Sordariomycetes_unclassified) at the end of the compost. In contrast, the SMS-PM showed an increased bacterial diversity with anti-pathogen ( Pseudomonas ). The results indicated that the addition of pig manure improved the decomposition of refractory carbon from the spent mushroom substrate and promoted the maturity and nutritional content of the compost product.